Analyse comparée des profils professionnels dans les secteurs liés á l`environnement : études de cas en Italie, en France et en Gréce - Boldrini, Fabrizio [Verfasser] (Office des publications officielles des Communautés européennes, 2002)
"This study, undertaken in parallel in three European Union countries, aims to analyse the most significant professional figures in the environmental sector in both the public and private domains, within and outside enterprises, and relating to small and medium sized businesses. This work amplifies and extends research previously undertaken by CEDEFOP in 1998, which evaluated the impact of qualitative and quantitative changes in the labour market, relating to environmental protection. It also examines the new professional profiles that have become necessary as a result of the changes as well as the levels of qualification concerned with the developments in progress. The intentions of this work are to: evaluate in advance the changes to competencies in the environmental field in order to adapt the supply and demand of skill formation; and to verify, in view of the development of 'green activities', existing levels and methods of skill formation and to judge their adequacy to deal with the change in work and explicit and implicit skill formation demands." (VOCED, http://www.voced.edu.au/td/tnc_72.414)
Keywords: G 1.2.3.1 Potenziale; S 6.4.8.1 Umweltberufe; I 2.2.1 Westeuropa; Qualifikationsprofil; Umweltberuf; Internationaler Vergleich; Frankreich; Italien; Griechenland